Complete mitogenome and phylogenetic analysis of Hyalinocerus flavoscutatus Cai and Shen 1998 (Hemiptera: Eurymelinae: Idiocerini) - Shijia Zhu; Mengrong Guo; Hui Liu; Jiajia Wang (Mitochondrial DNA. Part B. Resources, 2024)
This study presents the initial sequencing and characterization of the complete mitochondrial genome (mitogenome) of Hyalinocerus flavoscutatus, making the first comprehensive exploration of the mitogenome in the Hyalinocerus. Utilizing next-generation sequencing techniques, we identified a circular DNA molecule spanning 15,307 bp. The mitogenome comprises 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and a primary non-coding region. Maximum likelihood phylogenetic evaluation, based on 13 protein-coding genes and two ribosomal RNA genes, robustly supports H. flavoscutatus as the basal group within Idiocerini. This research unveils valuable insights into the mitogenome of H. flavoscutatus and enhances our understanding of phylogenetic placement within the broader context of related tribes.